ANALISIS EFEKTIVITAS IMPLEMENTASI KURIKULUM 2013 : Survey pada Guru Ekonomi SMA di Bandung Raya - Ilhamsyah Maulana, - (2018)
Penelitianinidilaksanakanseiringdenganimplementasikurikulum 2013. MeskipunKurikulum 2013 telahdisusunsecaraterencanadanmatang, akantetapitingkatefektivitasimplementasikurikulum 2013 inimasihdipertanyakan. Olehsebabitu, penelitianinibertujuanuntukmengetahuicapaianefektivitasimplementasikurikulum 2013 oleh guru matapelajaranekonomi, sertamenjelaskanpengaruhkompetensi guru (pedagogik, profesional, sosial, danpribadi) terhadapefektivitasimplementasikurikulum 2013. Metodepenelitian yang digunakandalampenelitianiniadalahdeskriptif-eksplanatori. Subjekpenelitianiniadalah Guru Ekonomi SMA di Bandung Raya denganjumlah 81 guru. Teknikpengumpulan data yang digunakanadalahkuisioner online, studidokumentasi, danstudi literature. Teknikanalisis data yang digunakanadalahujiregresiliniearbergandadenganbantuanSoftware IBM SPSS 23. Hasilpenelitianmenunjukkanefektivitasimplementasikurikulum 2013 masihdibawahskor ideal, artinyaimplementasikurikulum 2013 padamatapelajaranekonomibelumefektif. Selainitu, efektivitasimplementasikurikulum 2013 inilebihdominandipengaruhiolehkompetensipedagogik guru dibandingkandengankompetensilainnya;---This research was conducted along with the implementation of curriculum 2013. Although the Curriculum 2013 had prepared in well-planned, but in its implementation can be inconsistent or in this case does not work effectively. Therefore, this study aimed to determine the effectiveness of the implementation of curriculum 2013 by economics teacher in Bandung Raya, and to know the influence of teachers' competencies (pedagogical, profesional, social, personal) on the effectiveness of the implementation of curriculum 2013. The research method used in this research was descriptive-explanatory. The subject of this research was economics teacher in Bandung Raya with the number of 81 teachers. Data collection techniques used were online questionnaire, documentation and literature studies. Data analysis technique used was the calculation of frequency, percentage, cross tabulation, and multiple linear regression test with the help of IBM Software SPSS 23. The results showed the effectiveness of the implementation of curriculum is still below the ideal score, meaning that the implementation of curriculum 2013 on economics subject has not been effective. The effectiveness of the implementation of Curriculum 2013 on economics subject was more dominantly affected by teacher's pedagogical competence compared to other competencies.